Report of the Managing Director to the Board of Governors and to the Executive Board Pursuant to Article XVIII, Section 4e. (Policy Papers; Policy Paper ;, 2016)
This report is submitted pursuant the provisions of the Articles of Agreement relating to a general allocation or cancellation of Special Drawing Rights (SDR). The Articles provide for periodic consideration and decisions on SDR allocations or cancellations in the context of consecutive basic periods of normally five years of duration (Article XVIII, Section 2(a)). The Tenth Basic Period for a general allocation or cancellation of SDRs began on January 1, 2012 and is scheduled to end on December 31, 2016. The Eleventh Basic Period will commence on January 1, 2017.